Partial Treponema spp. as candidate probiotics for rumen methane mitigation revealed by a module-based activity index - Wang, Wei; Chen, Xiaoyun; Fang, Donghui; Li, Linxiang; Yueda, A. G.; Gan, Jia; Deng, Xiaodong; Ma, Xiaoqin; Chen, Ying; Shi, Yi; He, Fang; Wu, Changfeng; et al. (Frontiers in Veterinary Science, 2025)
IntroductionMethane emissions from ruminants, driven by methanogenic archaea, are a major source of greenhouse gases. Current strategies often rely on metagenomic (MG) abundance as a proxy for methanogenic potential, despite evidence of a disconnect with in-situ activity.MethodsWe analyzed paired MG and meta-transcriptomic (MT) datasets from 48 bovine rumen samples. Comparative analyses were performed to assess microbial taxonomic abundance versus transcriptional activity. A Methanogenesis Pathway Expression Activity Index (MPEAI) was developed by integrating expression of four KEGG modules, and Random Forest modeling was applied to identify microbial taxa associated with MPEAI.ResultsMG and MT profiles showed incongruence in both microbial community composition and diversity, with MT revealing reduced archaeal transcriptional activity. Dominant archaeal genera (Methanobrevibacter, Methanocaldococcus) were transcriptionally suppressed relative to MG abundance (p < 0.001). In contrast, methanogenesis modules (M00356, M00567, M00357, M00563) exhibited higher expression in MT than MG (p < 0.0001), indicating pathway-level hyperactivity despite archaeal suppression. Random Forest analysis linked MPEAI variation to several Treponema species, which showed significant negative correlations with methanogenic pathway activity (r = −0.36 to −0.57, p < 0.01).ConclusionRumen methanogenesis is regulated by functional pathway activity rather than archaeal abundance. The consistent negative associations of Treponema species with methanogenesis highlight their potential as probiotic candidates for methane mitigation and underscore bacterial-archaeal interactions in shaping rumen methane production.